Tensegrity : structural systems for the future - Motro, Rene, 1946- (Kogan Page Science, 2003)
The word tensegrity results from the contraction of tensional and integrity, a word created by Richard Buckminster Fuller. He went on to describe tensegrity structures as islands of compression in an ocean of tension, and Ren Motro has developed a comprehensive definition which is systems in a stable self equilibriated system comprising a discontinuous set of compressed components inside a continuum of tensioned components. This publication represents the life work of a leading exponent of a revolutionary and exciting method of structural design. * Represents the life work of a leading exponent of a revolutionary and exciting method of structural design * Applicable to architecture as an established structural system, can also be applied to other fields * Design professionals will be able to design better structures. Interested non-professionals will experience the great pleasure of being able to say "I understand why the Hisshorn tower stands up."